2012
DOI: 10.1177/1088767912438711
|View full text |Cite
|
Sign up to set email alerts
|

Tough on Crime or Beating the System

Abstract: Homicide defendants asserting the insanity defense make a volatile combination. Numerous studies review inmates with murder convictions, yet the literature is not rich regarding defendants found not guilty by reason of insanity (NGRI) for murder. This study analyzes 27 years of insanity acquittals in Missouri, finding significant differences between those defendants found NGRI for murder and those found NGRI for other crimes. The get-tough-on-crime initiatives found in the criminal justice system may have led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A recent structured review demonstrated that the odds of perpetration of any violent behavior increased substantially when a variety of mental disorders (e.g., schizophrenia, bipolar disorder, ADHD), personality disorders, or substance use was present (Whiting et al., 2021); a specific link between psychosis and violence has also been supported (Douglas et al., 2009). As individuals who are found NCRMD in Canada (Crocker et al., 2015a) and internationally (Dirks‐Linhorst & Kondrat, 2012) are most frequently diagnosed with a psychotic disorder, the role of the different symptoms of psychosis in targeted violence is an important area of inquiry.…”
Section: Introductionmentioning
confidence: 99%
“…A recent structured review demonstrated that the odds of perpetration of any violent behavior increased substantially when a variety of mental disorders (e.g., schizophrenia, bipolar disorder, ADHD), personality disorders, or substance use was present (Whiting et al., 2021); a specific link between psychosis and violence has also been supported (Douglas et al., 2009). As individuals who are found NCRMD in Canada (Crocker et al., 2015a) and internationally (Dirks‐Linhorst & Kondrat, 2012) are most frequently diagnosed with a psychotic disorder, the role of the different symptoms of psychosis in targeted violence is an important area of inquiry.…”
Section: Introductionmentioning
confidence: 99%